The Theme of Pandemic in Cinema Discourse (on the Example of the film „The Seventh Seal“ by I. Bergman (1957). Literature and Pandemic. Historical and Thematic Experience: XV International Symposium Contemporary Issues of Literary Studies. Theses. - Nikoriak, Natalia; Tychinina, Alyona (Tbilisi: TSU Shota Rustaveli Institute of Georgian Literature, 2021)
The theme of pandemic in arts (pestilence, plague, viruses) has always been quite relevant. Almost each generation that faced the similar catastrophes left rather detailed descriptions of such catastrophes in literary works. For instance: “The Iliad” (pestilence), “The Decameron” by G. Boccaccio (plague), “The Canterbury Tales” by J. Chaucer (plague), “A Journal of the Plague Year” by D. Defoe, “The Plague” by A. Camus, “Pale Horse, Pale Rider” by K. A. Porter (Spanish flu) and numerous modern variations, like “I am the Doorway by S. King (virus), “The Eyes of Darkness” by D. Koontz (virus), “Doomsday Book” by C. Willis (plague), “Blindness” by J. Saramago (virus), “The History of Pride” by L. Zoja (epidemic), “Snow Crash” by N. Stephenson (virus), “The Year of the Flood” by M. Atwood (epidemic), “Station Eleven” by J. Mandel (pandemic), etc. It is essential that literature does not only actively responds to global social issues like pandemic, but quite frequently predicts them. No wonder that cinema also lays particular emphasis on this theme, turning at first to the prior literary texts (film adaptations: The “Decameron” by P. Pasolini (1971), “The Andromeda Strain” by R. Wise (1971), “Death in Venice” by L. Visconti (1971), “The Plague” by L. Puenzo (1992), “The Painted Veil” by J. Karen (2006)), and later releasing its own creative versions: “Shivers” by D. Cronenberg (1975), “Epidemic” by L. Trier (1987), “Twelve Monkeys” by T. Gilliam (1995), “28 Days Later” by D. Boyle ” (2002), “Pontypool” by B. McDonald (2008), “Carriers” by D. and A. Pastor (2009), “Contagion” by S. Soderbergh (2011). Among numerous cinema versions on the theme, particular significance is attached to a religious-philosophical parable “The Seventh Seal” by the Swedish director I. Bergman (1957). The scenario of this film is based on I. Bergman’s one-act play “Painting on Wood” (1954-1955). However, the literary constituent of the film under studies is not restricted to this play only. On the whole, it is important to point out a rich intertextual nature of the film-parable. First of all, it is biblical intertext that attracts peculiar attention – the “Book of Revelation” (Apocalypse of John, Revelation to John or Revelation from Jesus Christ) and “The Plague” by A. Camus. In addition, the author also focuses on the epos of the Middle Ages, which is adequately reflected in the personosphere, chronotope, and intermedial insertions. The issue of pandemic, viewed in the film, describes its matrix in a very special way, gradually leading the viewer to decoding the parable-allegoric element. Consequently, the film is perceived as a kind of a “culturological encyclopedia” presenting difficult times in human history, whereby mankind faced the danger of either bubonic plague, or inquisition, or mass hysteria.
Keywords: pandemic; movie parable; intermediate code; “The Seventh Seal”; I. Bergman